2023
DOI: 10.1021/acscatal.2c04845
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Supramolecular Assembly for Superior CO2Photoreduction

Abstract: Coordination-driven metallo-supramolecular assemblies are potentially efficient catalysts in photocatalytic CO2 reduction. However, the relationship between morphology and photocatalytic performance remains barely explored. In this work, three metallo-supramolecular assemblies composed of Zn2+ and a flexible tris(terpyridine) ligand have been prepared for noble metal-free CO2 photoreduction on the basis of metal–ligand coordination, hydrogen bonding, and π–π stacking. The three assemblies possess distinct self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
0
16
0
3
Order By: Relevance
“…To compare with other redox potentials conveniently, CB potentials of Py3tpyZn and Ph3tpyZn are also given as −0.68 and −0.98 V vs. NHE (E(NHE) = E(SCE) + 0.24 V). 20,47 As shown in Fig. 2, CB potentials of Py3tpyZn and Ph3tpyZn are both more negative than redox potentials of E(CO 2 /CO) (−0.53 V) and E(O 2 /O 2 c − ) (−0.33 V).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…To compare with other redox potentials conveniently, CB potentials of Py3tpyZn and Ph3tpyZn are also given as −0.68 and −0.98 V vs. NHE (E(NHE) = E(SCE) + 0.24 V). 20,47 As shown in Fig. 2, CB potentials of Py3tpyZn and Ph3tpyZn are both more negative than redox potentials of E(CO 2 /CO) (−0.53 V) and E(O 2 /O 2 c − ) (−0.33 V).…”
Section: Resultsmentioning
confidence: 89%
“…Initially, the photocatalytic CO 2 reduction experiment was conducted with Py3tpyZn as the catalyst and triethylamine (TEA) as the sacricial electron donor in the presence of an organic photosensitizer 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) that we have recently used in CO 2 photoreduction. 20,[52][53][54] As shown in Table S2, † 1.23 mmol of CO was generated and only 0.05 mmol of H 2 was found, giving a high selectivity of 96%. Liquid products were not detected by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that individual clusters have better catalytic activity than the corresponding MOFs. Many studies have demonstrated that the morphology of a catalyst can affect its catalytic activity, which is related to the exposure of active sites. , The better catalytic activity of clusters compared to MOFs is due to the fact that individual clusters are homogeneous catalysts conducive to active catalytic sites contacting with PS and reactants. The reactants and products are dissolved in the solution in common catalytic reactions.…”
Section: Resultsmentioning
confidence: 99%